Pengaruh Bauran Pemasaran terhadap Penjualan Motor Bekas pada Dealer Syaf Motor di Bukittinggi - Nurfitriyenni, Nurfitriyenni (Jurusan PIPS FKIP UMMY Solok, 2019)
This study aims to determine the effect of products, prices, promotions, and locations on used motorcycle sales at Syaf Motor dealerships in Bukittinggi City. This research is a quantitative study using SPSS version 16.00. Sampling in this study using probability sampling techniques with simple random sampling method, which is each individual has the same opportunity to be the subject of research. The number of samples to be taken in this study can be calculated using the Slovin formula, the sample to be used in this study is 60 people. Data collection using questionnaire methods and consumer techniques. Data collection using questionnaire methods and data analysis techniques using Multiple Linear Regression. The results of the analysis show that products, prices, promotions, and locations have a positive and significant influence on sales, both partially and simultaneously. The most dominant variable affecting sales is the product. From this study, it was concluded that the four variables used provided 54.8% of the influence on sales, the remaining amounted to 45, 20% influenced by other factors not used in this study.